Governmental Accounting Innovations: An Application of FMR Model in Indonesia - SAID MUNIRUDDIN (The Indonesian Journal of Accounting Research, 2013)
Indonesia has undergone years of reform of its Governmental Accounting System. A comprehensive framework is then needed to understand the overall process and results of the reform. With the help of the latest version of the internationally recognized model of Comparative International Governmental Accounting Research (CICAR), namely the Financial Management Reform Model (FMR), also called Lüder’s Contingency Model, this article attempts to find this big picture of “why is Indonesian national governmental accounting changing?”, “what factors influence the reform?”, “what are the reform concepts?”, “how is the reform implemented?”, and “what are the outcomes of the reform?”. This paper looks at the effects of Indonesian reformation of 1998 and its subsequent national governmental accounting changes until 2010. In this qualitative approach, a desk research technique is used to collect various printed and online data. A content analysis, which is more focused on the thematic analysis of text, is then employed in examining of related texts, government documents, publications, and regulations. The assessment of FMR Model with regard to the Indonesian national government has generally confirmed the elements found in the Contingency Theory while the overall condition is rather favorable for the current reform as well as for continuing to further stages. By highlighting various variables influencing governmental accounting reform in Indonesia, this initial research makes a contribution to Indonesian public accounting literature. Further comprehensive and detail research is highly recommended in order to have a comprehensive and clearer explanation of the reform.